Methodical Recommendations from EC (Educational Component) "Geopolitics and Geostrategy" - Kopachinska, Galina Vasylivna (My University, 2024)
The educational and methodical publication from the EC "Geopolitics and Geostrategy", contains methodological recommendations on this discipline for students of the Faculty of International Relations: an explanatory note; syllabus of the academic discipline; questions for seminars and for the exam; information minimum for understanding the course and test questions for self-control, which will be useful during the study; independent training of bachelors; preparation for seminars and the course exam. Recommended for students of specialty 291 "International relations, public communications and regional studies", educational and professional program "International relations", educational degree "bachelor" of the Faculty of International Relations of Lesia Ukrainka Volyn National University.
Keywords: Theoretical foundations of the study of geopolitics and geostrategy; Global and regional applied geopolitics; formation of geopolitics of Ukraine; 327:911(072)